2012
DOI: 10.1021/ja303251f
|View full text |Cite
|
Sign up to set email alerts
|

Click-Modified Anandamide siRNA Enables Delivery and Gene Silencing in Neuronal and Immune Cells

Abstract: Click chemistry of alkyne-modified RNA with different receptor ligand azides was used to prepare 3'-folate, 3'-cholesterol, and, as a new entity, 3'-anandamide-modified RNA in high yields and excellent purity. The anandamide-modified RNA shows surprisingly high transfection properties and enables the delivery of siRNA even into difficult-to-transfect RBL-2H3 cells which model neuronal uptake. Furthermore, the system was employed in human immune cells (BJAB), demonstrating silencing effects similar to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 49 publications
1
67
0
4
Order By: Relevance
“…Trivalent but not monovalent conjugates provided effective delivery of the SSO. Anandamide, a ligand for cannabinoid receptors, was conjugated to siRNA via click chemistry (242). These conjugates provided effective functional delivery of siRNA to several cell types.…”
Section: Approaches To Deliverymentioning
confidence: 99%
“…Trivalent but not monovalent conjugates provided effective delivery of the SSO. Anandamide, a ligand for cannabinoid receptors, was conjugated to siRNA via click chemistry (242). These conjugates provided effective functional delivery of siRNA to several cell types.…”
Section: Approaches To Deliverymentioning
confidence: 99%
“…Anandamide recognizes the cannabinoid receptor which is highly expressed on neuronal and immune cells. A corresponding siRNA conjugate was successfully taken up in these cultured cells and resulted in down regulation of the siRNA-targeted gene, although high concentrations were required [145].…”
Section: Targets and Ligands For Tumorsmentioning
confidence: 99%
“…transferrin-antibody transferrin-targeted fusion peptide transferrin receptor  liposomes [110]  peptide/siRNA complexes [112] rabies virus glycoprotein (RVG) not identified nAChR, NCAM, and p75NTR are possible targets  peptide/siRNA complexes [113]  polyethyleneimine complexes [115]  liposomes [116]  PAMAM nanoparticles [117]  targeted exosomes [114] LEUKOCYTES integrin-antibody integrins  protamine-antibody/siRNA complexes [126]  liposomes [127] TUMOR TISSUES folate folate-receptor  polythyleneimine complexes [135][136][137]  PEG-siRNA conjugate [138]  self-assembled nanoparticles [145] hyaluronic acid CD44  hyaluronic acid-graft-poly(dimethylaminoethyl methacrylate) (HPD) conjugate complexes [140] …”
Section: Blood-brain-barriermentioning
confidence: 99%
“…Much work has been carried out on modifying cationic lipids for use in gene transfection, to determine if there is a ‘best’ chain length. 31 However, solid conclusions are rarely obtained, for the conclusions of these studies are frequently contradictory. In this study, CDL14 and CDO14 showed superior siRNA delivery.…”
Section: Resultsmentioning
confidence: 99%